Ergonomic Design of Table and Chair at Cafe Gajahmada, Mojokerto - Enny Aryanny; Atim Puji Lesmono; Rizqi Novita Sari; Erlina Purnamawaty (Future Science)
Cafe Gajahmada is a cafe on the main street of Mojokerto which has a minimalist architectural style. This cafe provides fast food and is equipped with Wi-Fi so that visitors can surf the internet for free and become an interesting place to socialize. Along with the times, existing tables and chairs do not meet ergonomic standards because when visitors use notebooks, sometimes spills occur so that the water hits the notebook. There is no safe place to put drinks because the design of the tables and chairs is only intended as a place to eat. In addition, the chairs used is not ergonomic, where, when sitting, there is discomfort in the hips because the seat design does not match the dimensions of the visitor's body, and also the material is made of hard material, so it is not comfortable to sit for long with the intensity of time. This study aims to design an ergonomic cafe table and chair to provide comfort to visitors when using it. Based on the results of the study, the size of an ergonomic cafe table and chair is table height is 78 cm, and table width is 47 cm, table length is 72 cm, seat height is 44 cm, seat width is 38 cm, seat length is 40 cm, chair back width is 41 cm, and the seatback height is 55 cm.